2021
DOI: 10.1371/journal.pone.0252828
|View full text |Cite
|
Sign up to set email alerts
|

Family aggregation of sleep characteristics: Results of the Heinz Nixdorf Recall and the Multi-Generation Study

Abstract: Introduction Poor sleep is a risk factor for adverse health events. For health prevention, it may be helpful to know whether poor sleep or sleep disorders in individuals are associated with sleep problems in their partners or children. Methods In the MultiGeneration Study (MGS, conducted from 2013 to 2016), 1237 partners (aged 27 to 90 years) and 1660 adult children (aged 18 to 66 years) of index persons were recruited. Index persons are participants of the Heinz Nixdorf Recall Study, a population-based coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Details about the study can be found in Caspers, et al [ 18 ]. Briefly, the 1000BRAINS sample is drawn from the 10-year follow-up of the Heinz Nixdorf Recall (HNR) study [ 19 ] and the Heinz Nixdorf Multigeneration Study (MGS) [ 20 ]. The ongoing population-based prospective HNR study collects data on health, social and environmental risk factors and cardiovascular outcomes in the Ruhr metropolitan region.…”
Section: Methodsmentioning
confidence: 99%
“…Details about the study can be found in Caspers, et al [ 18 ]. Briefly, the 1000BRAINS sample is drawn from the 10-year follow-up of the Heinz Nixdorf Recall (HNR) study [ 19 ] and the Heinz Nixdorf Multigeneration Study (MGS) [ 20 ]. The ongoing population-based prospective HNR study collects data on health, social and environmental risk factors and cardiovascular outcomes in the Ruhr metropolitan region.…”
Section: Methodsmentioning
confidence: 99%